Using digital tools for a sustainable transition in small- scale livestock farming in Brazil: Results from workshops with local action partners - Oliviera, Denis; Laurens, Violaine; Pereira, Mariana (2024)
This report summarizes the results of three workshops about the use of digital tools to support the sustainable transition of family livestock farming in Brazil, organized by Solidaridad in November 2024 in the context of the Inclusive Digital Tools (ATDT) project. The Inclusive Digital Tools Project (ATDT) aims to make digital technologies accessible to all, to integrate resilience and climate change mitigation with agroecological objectives and train farmers to develop new practices. It is an initiative of the Agroecological Transitions Program for Building Resilient and Inclusive Agricultural & Food Systems (TRANSITIONS), funded by the European Union through its DeSIRA initiative and managed by the International Fund for Agricultural Development (IFAD). The TRANSITIONS program seeks to support large-scale agroecological transitions through the development and adoption of multidimensional performance indicators for food and agricultural systems, inclusive digital tools, incentives and public and private sector investments for food systems. Solidaridad has been working in the South of Pará, along the Transamazonian highway for over 10 years, supporting rural families in the adoption of better production practices with the objective of boosting family income while reducing carbon emissions and deforestation. As part of the ATDT project, Solidaridad conducted a highly collaborative co-creation process involving over 90 extension staff, farmers, and IT developers that resulted in the development of a mobile application called Solis. Launched publicly in October 2024, this innovative tool replicates social media mechanisms to enable farmers and extensionists to continuously engage in the co-creation of knowledge, providing them with the opportunity to share their own experiences and insights. With a simple and intuitive interface, Solis allows users to publish videos—whether produced by themselves or shared from other social networks—on techniques, experiences, and knowledge related to agricultural production, thereby fostering an interactive environment for the generation and dissemination of local knowledge. As an open application available to any user with the Android operating system, Solis can also be accessed by other stakeholders interested in exchanging knowledge and techniques for more sustainable agricultural production. In this way, Solis serves as a valuable tool for promoting the ongoing exchange of information among small producers, researchers, policymakers, decision-makers, market agents, expand outreach of technical assistance, and support the transition from a traditional bottom-up approach to a more interactive, two-way communication model with farmers. In addition to the development of Solis, the ATDT project also resulted in the publication of a comprehensive training curriculum for sustainable livestock production. This curriculum outlines the methodology for co-creating locally relevant practices with farmers, extension staff, and experts, drawing on insights from its application in the Transamazon region. It includes a detailed overview of Solis, as well as practical guidance on using the platform to disseminate information about sustainable livestock farming practices. Following the launch of Solis and the publication of the curriculum, Solidaridad organized three workshops with key stakeholders in the livestock value chain at the municipal level in Novo Repartimento and at the state level in Pará and Mato Grosso. The workshops aimed to discuss how digital tools can support and accelerate the transition to a sustainable livestock production model, as well as gather suggestions from participants to make the Sustainability Curriculum and the Solis app useful and relevant in their local context. Attendees included representatives from municipal and state environmental and agricultural secretariats, farmer organizations, NGOs, private sector entities, and academic institutions. The objective of this report is to document and share key contributions from these stakeholders, with the hope that this will facilitate the adoption of the curriculum in other regions for the co-creation of relevant sustainable and agroecological practices tailored to the local context, as well as promote the use of Solis as a channel for the dissemination and sharing of knowledge about sustainable practices.